Sorghum grain stillage for pregnant gilts - Allee, G.L.; Koch, B.A.; Jackson, K. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Gilts during pregnancy consumed approximately 29 pounds of milo stillage per day, when fed only stillage. Availability of water did not affect stillage consumption. Gilts fed stillage consumed only 2.2 pounds of DM per day which was not enough to maintain body weight. Gilts fed all the stillage they would consume and one pound of the control diet made similar weight gains and had similar reproductive performance as gilts fed three pounds of the control diet. This suggests that the energy value of the milo stillage is similar to that of the control diet (1620 kcal DE/lb DM) for gilts during gestation.
Keywords: Swine; Sorghum grain stillage; Pregnant gilts